La Wally dramma lirico in four acts - Catalani, Alfredo 1854-1893 (Unitel GmbH & Co. KG, 2022)
Set in the Austrian state of Tyrol, La Wally tells the tragic story of a woman's love for her father's enemy, his trickery in seducing her, and the revenge wrought by her anger
Program and synopsis notes in English, German, and French (21 pages : illustrations ; 18 cm) in container
Interpreten: Izabela Matula (Wally). Leonardo Capalbo (Giuseppe Hagenbach). Acques Imbrailo (Vincenzo Gellner). Ilona Revolskaya (Walter). Alastair Miles (Stromminger). Zoltán Nagy (Il Pedone). Sofia Vinnik (Afra). Wiener Symphoniker. Arnold Schoenberg Chor. Erwin Ortner (Choreinstudierung). Andréas Orozco-Estrada (Dirigent)
Aufnahme: Wien, Theater an der Wien, November 2021
Keywords: Operas; Triangles (Interpersonal relations) / Drama; Man-woman relationships / Drama; Revenge / Drama; Hotelkeepers / Drama; Tyrol (Austria) / Drama; Hotelkeepers; Man-woman relationships; Revenge; Triangles (Interpersonal relations); Austria / Tyrol; Drama; Feature films; Filmed performances; Film; DVD-Video